Petrochronology of high-pressure granulite facies rocks from Southern Brasília Orogen, SE Brazil: Combining quantitative compositional mapping, single-element thermometry and geochronology - Fumes, Regiane Andrade [UNESP]; Luvizotto, George Luiz [UNESP]; Moraes, Renato; Lanari, Pierre; Valeriano, Claudio de Morisson; Zack, Thomas; Caddick, Mark J.; Simões, Luiz Sergio Amarante [UNESP] (Wiley, 2022)
We use a combination of several in situ techniques to assess the P-T-t path of high-pressure granulites from the Passos Nappe in the Southern Brasília Orogen (SE Brazil). Quantitative element mapping and single-element thermometers (Zr-in-rutile and Ti-in-quartz) are coupled with P-T pseudosections and monazite and rutile dating. Compositional and temperature maps, based on cathodoluminescence mapping and in situ analyses of Ti-in-quartz, are presented as a novel approach to evaluate crystallization temperature. The studied rocks have a pelitic protolith and record a peak pressure assemblage of garnet + kyanite + rutile + K-feldspar + quartz + melt ± plagioclase that formed at ~830°C and 1.2 GPa. Retrograde conditions of ~560°C and 0.6 GPa are determined based on the grossular content of garnet and the crystallization of biotite and ilmenite. Metamorphic peak conditions occurred ca. 635 Ma, according to monazite dating, with a younger date of ca. 615 Ma associated with later kyanite crystallization. Rutile ages of ca. 590 Ma are linked to the late retrograde stage (at ~600°C). Results show that the distribution of Ti-in-quartz is heterogeneous, decreasing in abundance towards the rim of crystals, though the higher temperatures constrained with Ti-in-quartz thermometry are broadly consistent with peak conditions. The peak pressure conditions are consistent with continental collision setting in the Southern Brasília Orogen and were followed by an early cooling/decompression stage and then by a slow cooling during exhumation and transport to shallower crustal levels.
Keywords: cathodoluminescence; P-T-t path; phase equilibrium modeling (THERMOCALC); single element thermometers; Western Gondwana; XMapTools